1999
DOI: 10.1097/00000542-199910000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Effects of Isoflurane on Movement Occurring after Noxious Stimulation 

Abstract: The results indicate that increasing anesthetic concentration from 0.6 to 0.9 MAC had little effect on the motor system controlling the force of limb movements, and the neural system generating repeated limb movements was depressed, consistent with a differential anesthetic effect at separate sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…Different anesthetic potencies of isoflurane on supraspinal or spinal structures have been reported. For isoflurane, the ratio of the righting-response ED50, an index of hypnosis, to MAC has been reported to have a mean value of 0.475 [6], and increasing the isoflurane concentration from 0.6 to 0.9 MAC was found to have little effect on the motor system [1]. In the present study, it was found that isoflurane inhalation at approximately two-thirds of MAC provided constant TF latency values on repeated testing.…”
Section: Discussionsupporting
confidence: 39%
“…Different anesthetic potencies of isoflurane on supraspinal or spinal structures have been reported. For isoflurane, the ratio of the righting-response ED50, an index of hypnosis, to MAC has been reported to have a mean value of 0.475 [6], and increasing the isoflurane concentration from 0.6 to 0.9 MAC was found to have little effect on the motor system [1]. In the present study, it was found that isoflurane inhalation at approximately two-thirds of MAC provided constant TF latency values on repeated testing.…”
Section: Discussionsupporting
confidence: 39%
“…Increasing halothane from 0.8 to 1.2 MAC further suppressed AUC windup to 34% of control, whereas increasing isoflurane did not further suppress AUC windup. The progressive depression of dorsal horn nociceptive processing at sub-MAC concentrations could partly account for the increase in stimulus frequency and intensity required to produce movement as isoflurane increases from 0 toward 1.0 MAC (14) and for the decrease in movement during supramaximal stimulation as isoflurane increases from 0.6 to 0.9 MAC (21).…”
Section: Discussionmentioning
confidence: 99%
“…In a crossover design (4), isoflurane or halothane was then administered in counterbalanced order such that each anesthetic was tested first in one half of the experiments. Windup responses were recorded during either isoflurane 0.6% (0.4 MAC), 1.1% (0.8 MAC), and 1.7% (1.2 MAC) or halothane 0.4% (0.4 MAC), 0.7% ( 0.8 MAC), and 1.1% (1.2 MAC); the approximate MAC fractions were based on previous studies from our laboratory (1,20,21). After changing the anesthetic concentration, we allowed equilibration times of at least 15 and 20 min for isoflurane and halothane, respectively, based on their blood-gas solubility coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…After the completion of the animal preparation, the inspired gas was converted to a mixture of air and O 2 (30 to 35% total O 2 ) and the end-tidal isoflurane concentration was adjusted to 1.3 ± 0.1% (Antognini et al, 1999;Masamoto et al, 2007a). At first, preliminary mapping with OIS (pre-mapping) was performed for the localization of the forepaw area in the primary somatosensory cortex.…”
Section: Animal Preparationmentioning
confidence: 99%